Bovine Tuberculosis in Cattle in the Highlands of Cameroon: Seroprevalence Estimates and Rates of Tuberculin Skin Test Reactors at Modified Cut-Offs - J. Awah-Ndukum; A. C. Kudi; G. S. Bah; G. Bradley; S. F. Tebug; P. L. Dickmu; H. N. Njakoi; W. N. Agharih (Veterinary Medicine International)
The aim of this study was to obtain epidemiological estimates of bovine tuberculosis (TB) prevalence in cattle in the highlands of Cameroon using two population-based tuberculin skin test (TST) surveys in the years 2009 and 2010. However, prior to the TST survey in 2010, blood was collected from already chosen cattle for serological assay. Anti-bovine TB antibodies was detected in 37.17% of tested animals and bovine TB prevalence estimates were 3.59%–7.48%, 8.92%–13.25%, 11.77%–17.26% and 13.14%–18.35% for comparative TST at ≥4 mm, ≥3 mm and ≥2 mm cut-off points and single TST, respectively. The agreement between TST and lateral flow was generally higher in TST positive than in TST negative subjects. The K coefficients were 0.119, 0.234, 0.251 and 0.254 for comparative TST at ≥4 mm, ≥3 mm and ≥2 mm cut-off points and the single TST groups, respectively. Chi square statistics revealed that strong (P<0.05; χ2>48) associations existed between seroprevalence rates and TST reactors. The study suggested that using lateral flow assay and TST at severe interpretations could improve the perception of bovine TB in Cameroon. The importance of defining TST at modified cut-offs and disease status by post-mortem detection and mycobacterial culture of TB lesions in local environments cannot be overemphasised.